A literature review of palm leaf manuscript conservation—Part 2: historic and current conservation treatments, boxing and storage, religious and ethical issues, recommendations for best practice. Issue 1 (2nd January 2023) - Wiland, Julia; Brown, Rick; Fuller, Lizzie; Havelock, Lea; Johnson, Jackie; Kenn, Dorothy; Kralka, Paulina; Muzart, Marya; Pollard, Jessica; Snowdon, Jenny
Abstract: The closure of the British Library during the 2020–2021 COVID-19 pandemic allowed the conservation department to undertake a treatment review of the conservation of palm leaf manuscripts in order to make better-informed decisions about the treatment of these complex objects. As part of the review a questionnaire was posted in 2020 to the Global Conservation Forum asking about the treatment of palm leaf manuscripts by others in the field. This two-part Literature Review uses the available literature and the survey results to address the wide range of issues inherent in the practical conservation of palm leaf materials. Part 1 began with an historic overview of palm leaf manuscripts and their production, leaf preparation methods, manuscript materials and media, palm leaf manuscripts at the British Library and the common types of damage found in such manuscripts. Part 2 details historic treatments and current conservation techniques as informed by our review and survey, as well as storage, religious and ethical issues. It concludes with two decision-making flowcharts, and our practical recommendations for conservators. The authors wish to share the collated information as widely as possible and help create greater continuity and consistency in palm leaf manuscript conservation by presenting recommendations for best practice for conservators who treat these amazing objects.